The construction of an indoor floor plan using a smartphone for future usage of blind indoor navigation - Jayakody, J.; Murray, Iain (Institute of Electrical and Electronics Engineers Inc., 2015)
Most blind people require assistance to navigate within unfamiliar environments as there is often insufficient information about the buildings available to them. To address aspects of this problem, this paper describes the “AccessBIM” model as an approach to facility management in which a digital representation of the indoor building features is used to facilitate the exchange and interoperability of real-time information in digital format which can assist blind people to independently access unfamiliar building indoor environments. The model driven architecture that can be implemented for way finding and data synchronization, generating, in real-time topological map, to assist vision impaired individuals to navigate known and unknown indoor environment.